2019
DOI: 10.1002/solr.201900192
|View full text |Cite
|
Sign up to set email alerts
|

Deepening the Valance Band Edges of NiOx Contacts by Alkaline Earth Metal Doping for Efficient Perovskite Photovoltaics with High Open‐Circuit Voltage

Abstract: Organometallic halide perovskite solar cells (PSCs) are rapidly evolving as the promising photovoltaic technologies with high record efficiency over 24%. The inorganic p‐type semiconductor NiOx is extensively used as important hole transport layers for the realization of stable and hysteresis‐free solar cells due to their good electronic properties, facile fabrication, and excellent chemical endurance. However, the critical issues of NiOx films including poor intrinsic conductivity and mismatched band alignmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…It was also found that the alkali earth metal heteroatoms in NiO x crystal lattice can improve the hole conductivity and downshift the valance band. Ge et al demonstrated versatile alkaline earth metal (Mg, Ca, Sr, Ba) doping strategies can significantly tailor the electrical properties of NiO x for inverted PSCs [58] . The valence band positions versus vacuum level could be calculated to be 5.04, 5.19, 5.29, 5.34 and 5.18 eV for the pristine NiO x , Mg:NiO x , Ca:NiO x , Sr:NiO x , and Ba:NiO x films, respectively.…”
Section: Alkali and Alkaline Earth Metal Dopingmentioning
confidence: 99%
“…It was also found that the alkali earth metal heteroatoms in NiO x crystal lattice can improve the hole conductivity and downshift the valance band. Ge et al demonstrated versatile alkaline earth metal (Mg, Ca, Sr, Ba) doping strategies can significantly tailor the electrical properties of NiO x for inverted PSCs [58] . The valence band positions versus vacuum level could be calculated to be 5.04, 5.19, 5.29, 5.34 and 5.18 eV for the pristine NiO x , Mg:NiO x , Ca:NiO x , Sr:NiO x , and Ba:NiO x films, respectively.…”
Section: Alkali and Alkaline Earth Metal Dopingmentioning
confidence: 99%
“…86 Moreover, dopants can inuence the optoelectronics of NiO by modifying its work function or ionisation potential, as in the case of alkaline-earth cation doping. 64,87 Before discussing in detail the doping mechanisms from alkaline and transition metal cations it is important to remark that non-metal and molecular doping is also suitable to improve the NiO performances. Zhou et al 88 reported the improvement of hole extraction from perovskite by including nitrogen (through guanidinium nitrate) in NiO.…”
Section: Doping Of Niomentioning
confidence: 99%
“…In fact, Ge et al, systematically investigated the effect of alkaline cation doping of NiO. [ 149 ] The main effect found was a downward shift of the VBM going from −5.04 eV for the pristine NiO to −5.19 eV with magnesium (Mg) and −5.29 eV with calcium (Ca) and −5.34 eV with strontium (Sr) (and barium, Ba, leading to −5.18 eV), with all the cations apparently substituting Ni, as suggested by the lattice expansion from XRD. At the same time, the conductivity was increased due to enhanced hole mobility.…”
Section: Transition Metal Oxides: Theoretical Investigations Of Electmentioning
confidence: 99%
“…[ 135 ] Copper doping has been later implemented in NiO NPs [ 262 ] for planar PSCs and also for the best‐performing NiO‐based mesoscopic PSCs to date (with efficiency approaching 20%). [ 136 ] Similarly, alkaline doping in NiO has also enhanced device performance, [ 149 ] primarily due to a downward shift of the VBM going from −5.04 eV for the pristine NiO to −5.19 eV with Mg and −5.29 eV with Ca and −5.34 eV with Sr (and barium leading to −5.18 eV), with all the cations apparently substituting Ni, as suggested by the lattice expansion from XRD. At the same time, the conductivity was increased due to enhanced hole mobility.…”
Section: Applications Of Tmos In Oscs and Pscsmentioning
confidence: 99%